1995
DOI: 10.1074/jbc.270.9.4205
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-dependent G Protein Coupling Function of Amyloid Transmembrane Precursor

Abstract: Amyloid precursor protein (APP), a transmembrane precursor of beta-amyloid, possesses a function whereby it associates with G(o) through its cytoplasmic His657-Lys676. Here we demonstrate that APP has a receptor function. In phospholipid vesicles consisting of baculovirally made APP695 and brain trimeric G(o), 22C11, a monoclonal antibody against the extracellular domain of APP, increased GTP gamma S binding and the turnover number of GTPase of G(o) without affecting its intrinsic GTPase activity. This effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
180
3
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(196 citation statements)
references
References 49 publications
12
180
3
1
Order By: Relevance
“…Interestingly enough, this sequence motif may be inverted in dDA1 (BXXABB). Other putative G protein-activating motifs, BBXB, [41] are, however, present in both the amino (KHVK) and middle (RRPK; KKFK) portions of this loop. In addition to the third cytoplasmic loop, sequences within the carboxyl-tail have been shown to determine G protein specificity [42].…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly enough, this sequence motif may be inverted in dDA1 (BXXABB). Other putative G protein-activating motifs, BBXB, [41] are, however, present in both the amino (KHVK) and middle (RRPK; KKFK) portions of this loop. In addition to the third cytoplasmic loop, sequences within the carboxyl-tail have been shown to determine G protein specificity [42].…”
Section: Resultsmentioning
confidence: 99%
“…These include the interaction with the heterotrimeric G protein Go (2), a 59-kDa ubiquitously expressed protein named APP-BP1 (3), the X11 protein (4), the neuron-abundant Fe65 protein, and an Fe65-like protein (4 -6). It was shown that intact APP binds to oligomeric Go protein and that the intracellular region of APP spanning residues 657-676 activates Go (2,7). Furthermore, the interaction of APP with a monoclonal antibody directed against its extracellular domain mimics a ligand-receptor binding that triggers Go activation (7).…”
mentioning
confidence: 99%
“…It was shown that intact APP binds to oligomeric Go protein and that the intracellular region of APP spanning residues 657-676 activates Go (2,7). Furthermore, the interaction of APP with a monoclonal antibody directed against its extracellular domain mimics a ligand-receptor binding that triggers Go activation (7). APP-BP1 interacts both in vitro and in vivo with the carboxyl-terminal region of APP, which represents its intracellular domain.…”
mentioning
confidence: 99%
“…Indeed, there is evidence that amyloid precursor protein, critical in the formation of amyloid plaques associated with Alzheimer's disease, functions as a receptor for G o (66,67). Since several functions for G o have been proposed, structural heterogeneity resulting from both alternative splicing and variable modification may allow G o to perform divergent functions.…”
Section: Discussionmentioning
confidence: 99%